EVALUATION OF SPORTS INFRASTRUCTURE MANAGEMENT AFTER THE IMPLEMENTATION OF NATIONAL SPORTS WEEK (PON) XX PAPUA 2021 - Hidayat, Abdurrahim; Widyaningsih, Heni; Wasan, Aan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Abstract This study evaluates the management of sports infrastructure facilities in this case the venue after the implementation of PON XX Papua seen from 7 aspect (1) Leadership; (2) Facilities Strategic and Operational Planning; (3) Customer Focus; (4) Assessment and Information Analyses; (5) Development and Management Human Resources; (6) Process Management; (7) Performance Result, the research methodology used the Facility Management Evaluation Program model. The population and samples in this study are officials or management staff as well as beneficiaries such as athletes and the community of ex-PON infrastructure facilities with purposive sampling techniques. Data collection techniques in this study by conducting interviews, observations and documentation studies. The results of this study show that the Management of Sports Infrastructure Facilities Management After the Implementation of PON XX carried out by the Youth Sports and Sports Office of Papua Province is very good. The existing policies to support the maintenance of the ex-PON venue have been very good and will continue to be evaluated and improved for more advanced sports in Papua Province. Keywords: Management; Sports infrastructure; Program Evaluation